Network traffic anomaly detection and prevention concepts, techniques, and tools - Bhuyan, Monowar H.; Bhattacharyya, Dhruba K.; Kalita, Jugal Kumar (Computer communications and networks, 2017)
This indispensable text/reference presents a comprehensive overview on the detection and prevention of anomalies in computer network traffic, from coverage of the fundamental theoretical concepts to in-depth analysis of systems and methods. Readers will benefit from invaluable practical guidance on how to design an intrusion detection technique and incorporate it into a system, as well as on how to analyze and correlate alerts without prior information